Exploring the Influence of Green Accounting on Sustainability Performance: A Literature Review - Tri Widyastuti (Greenation Research & Yayasan Global Resarch National, 2024)
This research explores the role of green accounting in promoting sustainability and its impact on organizational performance. Using the literature review method, relevant literature is selected and evaluated to extract important findings. The findings show that the implementation of green accounting can improve the financial performance of companies, especially in Indonesia and MSMEs in Central Java, by reducing production costs and strengthening the company's reputation. The results of this study provide insight into green accounting practices and the importance of environmental awareness in a business context, as well as its implications for investment decisions and customer perceptions.